Answer:
1 : 8
Step-by-step explanation:
Answer:
Step-by-step explanation:
9514 1404 393
Answer:
f^-1(x) = (x +4)/3
Step-by-step explanation:
The inverse function is found by swapping x and y, then solving for y.
y = 3x -4 . . . . . function y = f(x)
x = 3y -4 . . . . . inverse relation
x +4 = 3y . . . . add 4
(x +4)/3 = y . . . divide by 3. This is the inverse function
f^-1(x) = (x +4)/3
Original Price = Final Price / (100 - Discount)
So...
OP = 360 / 100 - 0.40
OP = 360 / 0.60
OP = 600
The original price is $600.
To check, do 600 - (600 * 0.40) in a calculator. You get 600 - 240 = 360, the discounted cost.